Violympic toán 8

Hạ Mặc Tịch
\(\frac{x+3}{12}+\frac{2x+46}{16}=\frac{3x+9}{36}+\frac{5x+81}{6}\)
✟şóı™βạ☪❖
9 tháng 4 2020 lúc 9:42

Bạn tìm Mẫu Thức Chung

Quy đồng

Khử mẫu

Tính

Kết Luận

Bình luận (0)
Trần Đăng Nhất
9 tháng 4 2020 lúc 9:45

\(\frac{x+3}{12}+\frac{2x+46}{16}=\frac{3x+9}{36}+\frac{5x+81}{6}\Leftrightarrow\frac{2\left(x+3\right)}{24}+\frac{\frac{3}{2}\left(2x+46\right)}{\frac{3}{2}.16}=\frac{\frac{2}{3}\left(3x+9\right)}{\frac{2}{3}.36}+\frac{4\left(5x+81\right)}{4.6}\)

\(\Leftrightarrow\frac{2\left(x+3\right)}{24}+\frac{3x+69}{24}=\frac{2x+6}{24}+\frac{20x+324}{24}\)\(\Leftrightarrow2x+6+3x+69=2x+6+20x+324\Leftrightarrow17x=-255\Leftrightarrow x=-\frac{255}{17}\)Vậy \(x=-\frac{255}{17}\)

Bình luận (0)

Các câu hỏi tương tự
Ren Nishiyama

1) \(\frac{3x-1}{4}+\frac{2x-3}{3}=\frac{x-1}{2}\) Mc : 12

\(\Leftrightarrow\) \(\frac{3.\left(3x-1\right)}{12}+\frac{4.\left(2x-3\right)}{12}=\frac{6.\left(x-1\right)}{12}\)

\(\Leftrightarrow\) 9x - 3 + 8x - 12 = 6x - 6

\(\Leftrightarrow\) 9x + 8x - 6x = 3 + 12 - 6

\(\Leftrightarrow\) 11x = 9

\(\Leftrightarrow\) x = 0,8

Vậy S = {0,8}

2) \(\frac{x+1}{2}-\frac{x+3}{12}=3-\frac{5-3x}{3}\) Mc : 12

\(\Leftrightarrow\) \(\frac{6.\left(x+1\right)}{12}-\frac{x+3}{12}=\frac{12.3}{12}-\frac{4.\left(5-3x\right)}{12}\)

\(\Leftrightarrow\) 6x + 6 - x + 3 = 36 - 20 - 12x

\(\Leftrightarrow\) 6x - x + 12x = -6 - 3 + 36 - 20

\(\Leftrightarrow\) 17x = 7

\(\Leftrightarrow\) x = \(\frac{7}{17}\)

Vậy S = {\(\frac{7}{17}\)}

3) x - \(\frac{x+1}{3}\) = \(\frac{2x-1}{5}\) Mc : 15

\(\Leftrightarrow\) \(\frac{15.x}{15}-\frac{5.\left(x+1\right)}{15}=\frac{3.\left(2x-1\right)}{15}\)

\(\Leftrightarrow\) 15x - 5x - 5 = 6x - 3

\(\Leftrightarrow\) 15x - 5x - 6x = 5 - 3

\(\Leftrightarrow\) 4x = 2

\(\Leftrightarrow\) x = \(\frac{2}{4}=\frac{1}{2}\)

Vậy S = {\(\frac{1}{2}\)}

4) \(\frac{2x+7}{3}-\frac{x-2}{4}=-2\) Mc : 12

\(\Leftrightarrow\) \(\frac{4.\left(2x+7\right)}{12}-\frac{3.\left(x-2\right)}{12}=\frac{12.\left(-2\right)}{12}\)

\(\Leftrightarrow\) 8x + 28 -3x + 6 = -24

\(\Leftrightarrow\) 8x - 3x = -28 - 6 -24

\(\Leftrightarrow\) 5x = -58

\(\Leftrightarrow\) x = -11,6

Vậy S = {-11,6}

5) \(\frac{2x-3}{4}-\frac{4x-5}{3}=\frac{5-x}{6}\) Mc : 12

\(\Leftrightarrow\) \(\frac{3.\left(2x-3\right)}{12}-\frac{4.\left(4x-5\right)}{12}=\frac{2.\left(5-x\right)}{12}\)

\(\Leftrightarrow\) 6x - 9 - 16x + 20 = 10 - 2x

\(\Leftrightarrow\) 6x - 16x + 2x = 9 - 20 + 10

\(\Leftrightarrow\) -8x = -1

\(\Leftrightarrow\) x = \(\frac{1}{8}\)

Vậy S = {\(\frac{1}{8}\)}

6) \(\frac{12x+1}{4}=\frac{9x+1}{3}-\frac{3-5x}{12}\) Mc : 12

\(\Leftrightarrow\frac{3.\left(12x+1\right)}{12}=\frac{4.\left(9x+1\right)}{12}-\frac{3-5x}{12}\)

\(\Leftrightarrow\) 36x + 3 = 36x + 4 - 3 + 5x

\(\Leftrightarrow\) 36x - 36x - 5x = -3 + 4 - 3

\(\Leftrightarrow\) -5x = -2

\(\Leftrightarrow x=\frac{2}{5}\)

7) \(\frac{x+6}{4}\) - \(\frac{x-2}{6}-\frac{x+1}{3}=0\) Mc : 12

\(\Leftrightarrow\) \(\frac{3.\left(x+6\right)}{12}-\frac{2.\left(x-2\right)}{12}-\frac{4.\left(x+1\right)}{12}=0\)

\(\Leftrightarrow\) 3x + 18 - 2x + 4 - 4x - 4 = 0

\(\Leftrightarrow\) 3x - 2x - 4x = -18 - 4 + 4

\(\Leftrightarrow\) -3x = -18

\(\Leftrightarrow\) x = 6

Vậy S = {6}

8) x\(^2\) - x - 6 = 0

\(\Leftrightarrow\) x\(^2\) + 2x - 3x - 6 = 0

\(\Leftrightarrow\) x.(x + 2) - 3.(x + 2) = 0

\(\Leftrightarrow\) (x - 3).(x + 2) = 0

\(\Leftrightarrow\) x - 3 = 0 hoặc x + 2 = 0

\(\Leftrightarrow\) x = 3 hoặc x = -2

Vậy S = {3; -2}

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN